Mainstreaming grain zinc and iron concentrations in CIMMYT wheat germplasm - Velu, Govindan; Singh, Ravi P.; Juliana, Philomin; Mondal, Suchismita; Bentley, Alison R. (Elsevier, 2022)
Genetic biofortification through breeding offers sustainable solution to the micronutrient malnutrition problems in the target countries. Great progress has been made in the past decade in transferring alleles for high-zinc (Zn) and iron (Fe) from diverse genetic resources into elite wheat breeding lines. However, the major challenge is to maintain simultaneous and high rates of genetic gains for grain yield and grain Zn to meet the food and nutritional security demands through the continuous delivery of biofortified varieties that are competitive to replace non-biofortified varieties successfully. Although a few intermediate effect QTL regions are identified for grain Zn, both yield and Zn content are quantitatively inherited. Increased breeding efforts and new approaches are therefore required to combine them in high frequency in CIMMYT's elite germplasm, ensuring that Zn levels are steadily increased to the required levels across the CIMMYT breeding pipelines. The addition of Zn as a core-trait will be achieved through significant acceleration in the breeding cycle, expanding population sizes, extensive Zn phenotyping, yield testing, phenotyping for biotic and abiotic stresses, molecular-assisted selection and genomic selection. While continuing to increase agronomic performance, high Zn alleles has been added as a core-trait. Eventually Zn content will be increased in the elite lines annually along with the frequency of elite lines with high yield and other agronomic traits that have potential to be released by partners. A genomics assisted “rapid cycle recurrent selection” scheme achieved through rapid generation advancement approaches are expected to enable CIMMYT wheat breeding program to mainstream grain Zn in the majority of elite lines in about 10 years.